Voices of care: unveiling patient journeys in primary care for hypertension and diabetes management in Kerala, India - Ravindranath, Ranjana; Sarma, P. Sankara; Sivasankaran, Sivasubramonian; Thankappan, Kavumpurathu Raman; Jeemon, Panniyammakal (Frontiers in Public Health, 2024)
Background Diabetes and hypertension are leading public health problems, particularly affecting low- and middle-income countries, with considerable variations in the care continuum between different age, socio-economic, and rural and urban groups. In this qualitative study, examining the factors affecting access to healthcare in Kerala, we aim to explore the healthcare-seeking pathways of people living with diabetes and hypertension. Methods We conducted 20 semi-structured interviews and one focus group discussion (FGD) on a purposive sample of people living with diabetes and hypertension. Participants were recruited at four primary care facilities in Malappuram district of Kerala. Interviews were transcribed and analyzed deductively and inductively using thematic analysis underpinned by Levesque et al.’s framework. Results The patient journey in managing diabetes and hypertension is complex, involving multiple entry and exit points within the healthcare system. Patients did not perceive Primary Health Centres (PHCs) as their initial points of access to healthcare, despite recognizing their value for specific services. Numerous social, cultural, economic, and health system determinants underpinned access to healthcare. These included limited patient knowledge of their condition, self-medication practices, lack of trust/support, high out-of-pocket expenditure, unavailability of medicines, physical distance to health facilities, and attitude of healthcare providers. Conclusion The study underscores the need to improve access to timely diagnosis, treatment, and ongoing care for diabetes and hypertension at the lower level of the healthcare system. Currently, primary healthcare services do not align with the “felt needs” of the community. Practical recommendations to address the social, cultural, economic, and health system determinants include enabling and empowering people with diabetes and hypertension and their families to engage in self-management, improving existing health information systems, ensuring the availability of diagnostics and first-line drug therapy for diabetes and hypertension, and encouraging the use of single-pill combination (SPC) medications to reduce pill burden. Ensuring equitable access to drugs may improve hypertension and diabetes control in most disadvantaged groups. Furthermore, a more comprehensive approach to healthcare policy that recognizes the interconnectedness of non-communicable diseases (NCDs) and their social determinants is essential.